2017
DOI: 10.1063/1.4993687
|View full text |Cite
|
Sign up to set email alerts
|

Pure-iron/iron-based-alloy hybrid soft magnetic powder cores compacted at ultra-high pressure

Abstract: We developed Fe/FeSiAl soft magnetic powder cores (SMCs) for realizing the miniaturization and high efficiency of an electromagnetic conversion coil in the high-frequency range (∼20 kHz). We found that Fe/FeSiAl SMCs can be formed with a higher density under higher compaction pressure than pure-iron SMCs. These SMCs delivered a saturation magnetic flux density of 1.7 T and iron loss (W1/20k) of 158 kW/m3. The proposed SMCs exhibited similar excellent characteristics even in block shapes, which are closer to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…However, the pure iron strips have higher saturation flux density than Mu-metal and electrical steel (saturation flux density of Mu-metal is 0.6 T). This observation is in consonance with earlier findings reported in the literature [ 38 , 40 , 41 ]. Therefore, the use of pure iron strips can be investigated for certain applications of magnetic flux shielding.…”
Section: Conclusion From Magnetic and Materials Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the pure iron strips have higher saturation flux density than Mu-metal and electrical steel (saturation flux density of Mu-metal is 0.6 T). This observation is in consonance with earlier findings reported in the literature [ 38 , 40 , 41 ]. Therefore, the use of pure iron strips can be investigated for certain applications of magnetic flux shielding.…”
Section: Conclusion From Magnetic and Materials Characterizationsupporting
confidence: 93%
“…The 99.8% pure iron foils fabricated with electro-deposition and cold rolling have better permeability (95.4% higher, the maximum relative permeability of electrical steel: 4000 and maximum relative permeability of the pure iron: 7818) than that of conventional Fe-Si electrical steel (Grade: ASTM 30F677). The observation for better magnetic permeability of the pure iron is in agreement with the earlier results reported in the references [ 38 , 39 , 40 ]. Further, the saturation magnetic flux density of the iron foils is better than electrical steel.…”
Section: Conclusion From Magnetic and Materials Characterizationsupporting
confidence: 93%
“…While pure iron is considered for manufacturing the magnetic core, the pole piece, relays, the speaker magnetic conductor, magnetic shield, etc. 58,59) Permanent magnet is considered for circuits where the magnetic excitation is provided by permanent magnets, or by DC or low-frequency ( < 10 Hz) pulsed current coils, with medium to high magnetic fluxes. 60) In low electrical power and electronic circuits, iron based soft magnets are used even at high frequencies ( < 200 Hz).…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…Some of the major commercial iron powder grades used in MIM technology. 58) Company Grade D50 (μm) AD (g/cm 3 ) Tap Density (g/cm 3 ) Femin (%) Cmax (%) Omax (%) Nmax (%) density from 1 200-1 450°C with increase in temperature. Tian et al 66) showed that the using carbonyl iron powder in MIM process, sintered density has improved significantly (above 1 393°C) using δ phase sintering.…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…In this paper, the cutting speed of pure iron material is analysed to determine the specific influence of speed on temperature in the process of pure iron material cutting. In the pure iron material cutting, the motor drive control is its running speed (Saito et al, 2018;Gong et al, 2020). By changing the cutting tool position and changing the installation angle of the blade on the cutter body, the cutting angle of the blade in the pure iron material part is increased to about 20°.…”
Section: Analysis Of Cutting Speed Of Pure Iron Materialsmentioning
confidence: 99%